Biomechanical Factors Associated With Achilles Tendinopathy and Medial Tibial Stress Syndrome in Runners. (September 2017) - Becker, James; James, Stanley; Wayner, Robert; Osternig, Louis; Chou, Li-Shan
Background: There is disagreement in the literature regarding whether the excessive excursion or velocity of rearfoot eversion is related to the development of 2 common running injuries: Achilles tendinopathy (AT) and medial tibial stress syndrome (MTSS). An alternative hypothesis suggests that the duration of rearfoot eversion may be an important factor. However, the duration of eversion has received relatively little attention in the biomechanics literature. Hypothesis: Runners with AT or MTSS will demonstrate a longer duration of eversion but not greater excursion or velocity of eversion compared with healthy controls. Study Design: Controlled laboratory study. Methods: Forty-two runners participated in this study (13 with AT, 8 with MTSS, and 21 matched controls). Participants were evaluated for lower extremity alignment and flexibility, after which a 3-dimensional kinematic and kinetic running gait analysis was performed. Differences between the 2 injuries and between injured and control participants were evaluated for flexibility and alignment, rearfoot kinematics, and 3 ground-reaction force metrics. Binary logistic regression was used to evaluate which variables best predicted membership in the injured group. Results: Injured participants, compared with controls, demonstrated higher standing tibia varus angles (8.67° ± 1.79° vs 6.76° ± 1.75°, respectively; P = .002), reduced static dorsiflexion range of motion (6.14° ± 5.04° vs 11.19° ± 5.10°, respectively; P = .002), more rearfoot eversion at heel-off (–6.47° ± 5.58° vs 1.07° ± 2.26°, respectively; P < .001), and a longer duration of eversion (86.02% ± 15.65% stance vs 59.12% ± 16.50% stance, respectively; P < .001). There were no differences in the excursion or velocity of eversion. The logistic regression (χ 2 = 20.84, P < .001) revealed that every 1% increase in the duration of eversion during the stance phase increased the odds of being in the injured group by 1.08 (95% CI, 1.023-1.141; P = .006). Conclusion: Compared with healthy controls, runners currently symptomatic with AT or MTSS have a longer duration of eversion but not greater excursion or velocity of eversion. Clinical Relevance: Static measures of the tibia varus angle and dorsiflexion range of motion, along with dynamic measures of the duration of eversion, may be useful for identifying runners at risk of sustaining AT or MTSS.